Seed Halopriming as an Effective Strategy to Enhance Salt Tolerance in Cakile maritima: Activation of Antioxidant and Genetic Responses - Roser Tolrà; Carlos González-Cobo; Isabel Corrales; Rosa Padilla; Mercè Llugany (Antioxidants)
Global food demand and insecurity are intensifying due to rapid population growth, the loss of arable land, climate change, and pollution. Among the critical challenges in global agriculture is soil salinization, in which high NaCl concentrations can severely inhibit germination and crop establishment. Cakile maritima, a halophyte from the Brassica genus, can tolerate salinity levels up to 400 mM NaCl, far exceeding the tolerance of most crops, making it a promising model for studying salt stress resistance. This study investigates the effects of seed halopriming as an effective strategy to enhance salt tolerance in C. maritima. The research evaluates germination rates, seedling establishment, mineral status, oxidative stress markers, and genetic responses under increasing NaCl concentrations. Halopriming with NaCl pre-activates the plant’s antioxidant defence mechanisms and upregulates stress-responsive genes, improving the plant’s resilience to saline conditions. While salinity caused significant physiological challenges, primed seeds demonstrated superior performance compared to non-primed controls, with enhanced germination and an improved tolerance to oxidative stress. These findings underscore the potential of halopriming as a cost-effective and sustainable technique to improve crop performance in saline environments. This study highlights the importance of advancing seed priming technologies for developing resilient crops to address global food security challenges in the face of climate change.